Encyclopedia of traditional Chinese medicines molecular structures, pharmacological activities, natural sources and applications. Vol. 2 - Xie, Guirong; Yan, Xinjian (Springer Berlin Heidelberg, 2011)
This set of six volumes provides a systematic and standardized description of 23,033 chemical components isolated from 6,926 medicinal plants, collected from 5,535 books/articles published in Chinese and international journals. A chemical structure with stereo-chemistry bonds is provided for each chemical component, in addition to conventional information, such as Chinese and English names, physical and chemical properties. It includes a name list of medicinal plants from which the chemical component was isolated. Furthermore, abundant pharmacological data for nearly 8,000 chemical components are presented, including experimental method, experimental animal, cell type, quantitative data, as well as control compound data. The seven indexes allow for complete cross-indexing. Regardless whether one searches for the molecular formula of a compound, the pharmacological activity of a compound, or the English name of a plant, the information in the book can be retrieved in multiple ways.